Effectiveness of Vestibular Rehabilitation for Patients with Degenerative Cerebellar Ataxia: A Retrospective Cohort Study - Lisa L. Heusel-Gillig; Courtney D. Hall (Brain Sciences, 2023)
Many patients with cerebellar ataxia have dizziness caused by oculomotor or peripheral vestibular deficits; however, there is little evidence supporting the use of vestibular rehabilitation for this population. The purpose of this study was to determine whether patients with degenerative cerebellar diseases improve following rehabilitation including vestibular exercises. A secondary aim was to identify variables associated with the outcomes. A retrospective chart review identified 42 ambulatory patients (23 men and 19 women; mean age = 54.5 ± 14.4 years) with cerebellar degeneration. Fourteen patients had ataxia only, twenty had ataxia and oculomotor abnormalities, and eight had ataxia with oculomotor and peripheral vestibular deficits. Patients received customized physical therapy including balance and gait training, as well as gaze stabilization and habituation exercises for vestibular hypofunction and motion-provoked dizziness. Primary outcome measures (Activities-specific Balance Confidence Scale, Tinetti Performance Oriented Mobility Assessment, Dynamic Gait index, and Sensory Organization Test) were evaluated at baseline and discharge. Patients improved (p < 0.05) on all outcome measures. Patients with vestibular deficits were seen for more visits compared to those with gait ataxia only (7.1 vs. 4.8 visits). This study provides evidence that patients with degenerative cerebellar disease improve in balance confidence, fall risk and sensory integration with therapy that includes vestibular rehabilitation.